EFECTO ANTIHIPERTENSIVO DEL EXTRACTO HIDROALCOHÓLICO DE LAS HOJAS DE Xanthium catharticum HBK “AMOR SECO” - Riveros, Zeyla (2015)
The present research core-experimental type was developed with the purpose of determining the antihypertensive effect of the hydroalcoholic extract of the leaves of Xanthium catharticum HBK. "dry love" in rats with induced hipertension because L-NAME. Using samples of Xanthium catharticum HBK collected in the Mollepata town center, located in Ayacucho region. Secondary metabolites present in the extract were determined using coloration and precipitation specific tests. To determine antihypertensive effect. It was used the induction method by chronic administration with L-NAME in 30 rats, randomly divided into six groups, the first one received distilled water; the second one, L-NAME 40 mg/kg; the third, fourth and fifth groups received L-NAME 40 mg/kg plus 100, 200, 400 mg/kg of extract, respectively; the sixth group received L-NAME 40 mg/kg plus captopril 100 mg/kg. Data were subjected to analysis of variance (ANOVA) with 95% confidence. The results indicated the presence of sesquiterpenes, alkaloids, phenolics, flavonoids, saponins, amino acids and anthocyanins compounds. The highest percentage of dose antihypertensive efficacy was 400 mg/kg 40,58%, while the groups of 100 and 200 mg/kg, got 33,96% and 28,54%, respectively, with a mildly hypertensive behavior (p<0,05) compared to control group receiving captopril 100 mg/kg with a decrease of 99,40%. It was conclude, that under experimental conditions, the hydroalcoholic extract of the leaves of Xanthium catharticum HBK "dry love" shown to have moderate antihypertensive effect.